Upaya Mencapai Kebahagiaan oleh Remaja Broken Home ‎Kelurahan Pasar Baru Kota Padang ‎Panjang - Ikhsan, Muhammad; Santosa, Budi (Lembaga Yasin AlSys, 2024)
This research is motivated by the existence of children from broken home families where their parents are divorced and the children do not live with both parents. The obligation to support their children is not carried out, these children feel unhappy like other friends who have intact parents. The aim of the research is to determine the efforts to achieve happiness by broken home teenagers in Pasar Baru district, Padang Panjang city. Descriptive qualitative research. Informants or people who act as information providers in this research are broken home teenagers in Pasar Baaru Village, Padang Paanjang City. Data were collected by interviews and then the data were analyzed using qualitative descriptive data analysis techniques and data triangulation, namely by comparing data obtained from observations and interviews. Based on the results of the research, it can be concluded that several efforts were made to achieve happiness by broken home teenagers, namely 1) having good relationships with other people, in this case, broken home teenagers have poor relationships with their parents, which can be seen from the fact that they rarely communicate as they should because their parents have separated. and live far away. 2) involve themselves in all aspects of life (full involvement), knowing that they are not fully involved either in making decisions about themselves, or in situations outside themselves. Teenagers are required to accept everything that has been chosen and arranged by their parents. Teenagers are also not involved in activities in. 3) finding the meaning of life, it is known that no one wants to be born into a disharmonious family. They only hope and aspire to help the mother who raised them.